2011
DOI: 10.2337/dc11-0182
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pharmacokinetic and Pharmacodynamic Profile of Rapid-Acting Insulin Using Needle-Free Jet Injection Technology

Abstract: OBJECTIVEInsulin administered by jet injectors is dispensed over a larger subcutaneous area than insulin injected with a syringe, which may facilitate a more rapid absorption. This study compared the pharmacologic profile of administration of insulin aspart by jet injection to that by conventional insulin pen.RESEARCH DESIGN AND METHODSEuglycemic glucose clamp tests were performed in 18 healthy volunteers after subcutaneous administration of 0.2 units/kg body wt of aspart, either administered by jet injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…Some studies have reported no local reactions after jet injections of insulin [3], whereas others have reported significant reaction, including immediate pain, delayed pain, bleeding, and hematomas [6,7]. In the present study, a trained nurse was arranged to perform the injection, and no hematomas, bruising, and bleeding were reported in the needle-free injection group.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Some studies have reported no local reactions after jet injections of insulin [3], whereas others have reported significant reaction, including immediate pain, delayed pain, bleeding, and hematomas [6,7]. In the present study, a trained nurse was arranged to perform the injection, and no hematomas, bruising, and bleeding were reported in the needle-free injection group.…”
Section: Discussionmentioning
confidence: 45%
“…A non-randomized study has evaluated profiles of insulin lispro using jet injector technology, but the sample size was small and the dose of insulin lispro was unreasonable [5]. A study conducted by Engwerda et al in 18 healthy volunteers, using a randomized, double-blind, double-dummy, crossover study design, found that GIR-Tmax as well as INS-Tmax were significantly shorter when aspart was injected by jet injection compared to conventional pen injection [3]. The results of our experiment were consistent with the above studies and further confirmed the advantage of the QS-M jet injector for delivering lispro in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter limits intra-and inter-individual reproducibility of the key pharmacokinetics parameters with obvious issues on formulation bioequivalence. This inconsistency seems to be device related because some of them have shown even better pharmacokinetic and pharmacodynamic parameters than conventional injection (Engwerda et al, 2011;Engwerda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%